Analysis of the legislation of the republic of kazakhstan on the prevention of gambling addiction (Journal of actual problems of jurisprudence, 2021)
The article is devoted to the analysis of the legislation of the Republic of Kazakhstan on counteracting the dependence of children and adolescents from gambling addiction (gambling addiction). The analysis is made in comparison with the countries which are the most experienced in the area as the authors believe. Gambling addiction is recognized as one of the most oppressing problems among adolescents and adults. Therefore, the world community has divided into two camps: some are on the path of prevention, and others on the path of emphasis on the use of punitive measures. The authors note that the domestic legislation contains elements of partial prevention, and the measures of legal responsibility do not fully correspond to the realities of the problem.The purpose of the article is a critical analysis of the measures taken by the government to combat gambling addiction among children and adults. The authors concluded that the steps taken are not entirely adequate and are not fully implemented. At the same time, it is noted that some steps have been taken.The value of the study and its practical value lies in the fact that the team of authors proposes a set of measures to improve counteracting gambling addiction among adolescents.The article was written within the framework of the project "Development and implementation of a set of measures for the prevention of Internet addiction and gambling among young people and children", implemented by the Regional Public Organization "United Children and Youth Organization" Zhas Ulan ".The practical significance of the article also lies in the fact that the attention of the state authorities will be drawn to the problems highlighted in the work and the proposals made will be implemented by making changes and additions to the current legislation of the Republic of Kazakhstan.Keywords: childhood, child rights, gambling addiction, addiction, information rights, children rights protection, crime prevention.